Arthropods in Colombia. An historical review - VALDERRAMA-HERNÁNDEZ, RAFAEL (Revista Colombiana de Entomología, 1999)
This historical review describes the events that have marked the relationships between arthropods and the Colombian people since the Pre Columbian period. with special emphasis in the conquest period and colonial period. The purpose is to give information to build the Medical Entomology Evolution in Colombia by narration. notes. chronicle and commentaries of the first chroniclers and historiographers in the country. grouped by specific subjects. It is reflected in the importance that arthropods all as disease agents for the American natives. the Spanish conquistadors and the colonial people. The bites of "zancudos" (mosquitoes), "jejenes-(gnats. black flies. month and sand flies), and "Pitos or chinches" (kissing hugs and hed bugs). or the infestation for flies larvae. "niguas- (chigger or sand flies) lice, and miles. impacted negatively over the population of XV. XVI. XVII and XVIII centuries: they imputed it with dread to bewitchments and witchcraft. miasmata and dismisses evil-blood or evil-eye, soul robbery or, simply hazard and bad luck. To start it is defined that and which are the most frequent and important arthropods. as a guide to developing the subsequent text. whereby it is verified how the arthropods that affected human health were omnipresent. since the early registration by the Spanish Chroniclers until the sporadic exploratory studies from The Epidemiological reality of some arthropods that sill effect today.